PENGARUH PERSEPSI PROFESI, KESADARAN ETIS DAN INDEPENDENSI AUDITOR TERHADAP KOMITMEN PROFESI AKUNTAN PUBLIK DI KOTA MEDAN - Rizqy Fadhlina Putri; Azhar Maksum; Erwin Abubakar (Jurnal Telaah dan Riset Akuntansi, 2013)
The objective of the research was to verify the influence of perception on profession, ethical awareness, and auditor’s independency, simultaneously and partially, on the commitment of public accountant’s profession in Medan. The data were gathered by conducting field survey, that is, by distributing questionnaires. The samples were taken by using purposive sampling technique. The data were primary data, obtained from giving 40 questionnaires to 20 public accountant offices in Medan. There were 34 obtained questionnaires which were processed. The data were analyzed by using multiple regression analysis with an SPSS 19 software program. The result of the research showed that, simultaneously (F test), the three independent variables (perception on profession, ethical awareness, and auditor’s independency) had significant influence on the commitment of public accountant’s profession. Partially, perception on profession, and auditor’s independency  influenced the commitment of public accountant’s profession respectively.Keywords : Perception on Profession, Ethical Awareness, Auditor’s Independency, Commitment of Profession